Team Boundary Work and Team Workload Demands: Their Interactive Effect on Team Vigor and Team Effectiveness - Leicht-Deobald, Ulrich (My University, 2022)
Drawing from team-level job demands-resources theory, we hypothesize that team workload demands moderate the positive link between team boundary work (i.e., boundary spanning and boundary buffering) and team effectiveness (i.e., team innovation and team performance), such that boundary work is more beneficial for team effectiveness when teams face higher team workload demands. Furthermore, we predict that this interaction occurs through increased team vigor, where team vigor is defined as an affective emergent state characterized by positive valences and high activation levels experienced by team members. We largely find support for our model across two field studies: a cross-sectional survey using three independent data sources (89 automotive research and development teams, including 724 team members, 89 team leaders, and 18 managers) and a time-lagged survey using two independent data sources (139 teams working in a Chinese utility company, including 640 team members and 139 team leaders). Our article contributes to team research by broadening our understanding of when and how team boundary work is associated with greater team effectiveness.
PUBLISHED
Keywords: boundary buffering; boundary spanning; team boundary work; team innovation; team performance; team vigor; team workload demands